Intraprocedural Imaging of Cardiovascular Interventions - Picard, Michael H.; Passeri, Jonathan J.; Dal-Bianco, Jacob P. (Springer International Publishing : Imprint: Springer, 2016)
This book presents a practical approach for the use of imaging across a wide variety of cardiovascular procedures. The use of catheter-based therapies is a rapidly expanding discipline for the minimally invasive treatment of many cardiac diseases. Cardiac ultrasound, particularly echocardiography, is utilized extensively to guide these therapies. This text teaches the key knowledge required for the use of ultrasound in many catheter- based cardiac therapies. In addition to the newest techniques such as transcatheter aortic valve replacement and transcatheter mitral valve edge-to-edge repair, it also includes guidance on more established procedures such as pericardiocentesis. Intraprocedural Imaging of Cardiovascular Interventions is an essential resource for clinicians and interventionalists to aid their understanding of imaging needs during various cardiovascular procedures. .